Pieces and players - Balliett, Blue (New York : Scholastic, Inc., 2016)
"When 13 high-value pieces of art are stolen from a secret museum, Calder, Petra and Tommy are grouped with two new companions to solve puzzles that are complicated by the clever Mrs. Sharpe." (Source: WorldCat)
Keywords: Art -- Juvenile fiction; Museums -- Juvenile fiction; Art -- Fiction